4, 4′-Di-tert-butyl-6-(1H-tetrazol-5-yl)-2, 2′-bipyridine: modification of a highly selective N-donor ligand for the separation of trivalent actinides from lanthanides. Issue 30 (20th July 2017) - Maiwald, Martin M.; Wagner, Anna T.; Kratsch, Jochen; Skerencak-Frech, Andrej; Trumm, Michael; Geist, Andreas; Roesky, Peter W.; Panak, Petra J.
Abstract : In the present work, the complexation and extraction behaviour of HN4 t bubipy towards An(iii ) and Ln(iii ) is studied by spectroscopy, solvent extraction, and QM calculations. Abstract : In the present work, the complexation and extraction behaviour of 4, 4′di- tert -butyl-6-(1 H -tetrazol-5-yl)-2, 2′-bipyridine (HN4 t bubipy) towards trivalent actinides (An(iii )) and lanthanides (Ln(iii )) is studied by spectroscopic methods, liquid–liquid extraction, and quantum chemical calculations. The ligand synthesis of HN4 t bubipy as well as its application in coordination chemistry of the 4f elements is described. Reaction of HN4 t bubipy with [Ln(NO3 )3 ·6H2 O] (Ln = Sm, Eu) results in [H2 N4 t bubipy] + [Ln(N4 t bubipy)(NO3 )3 (H2 O)] − . Both compounds have been characterized by single crystal X-ray diffraction. The solubility of the ligand in different organic solvents is determined, showing a high solubility in MeOH which decreases with the lipophilicity of the solvent. The p K a = 2.4 ± 0.2 of HN4 t bubipy in EtOH (4.4 vol% H2 O) is determined by absorption spectrophotometry. The complexation of Cm(iii ) and Eu(iii ) with HN4 t bubipy is studied by time resolved laser fluorescence spectroscopy (TRLFS). For both metal ions the formation of the complexes [M(N4 t bubipy) n ] 3− n with n = 2, 3 (M = Cm(iii ), Eu(iii )) is observed. Slightly higher conditional stability constants for Eu(iii ) (log  β ′2 (Eu(N4 t bubipy)2 + ) = 8.9 ± 0.3, log  β ′3 (Eu(N4 t bubipy)3 ) = 12.7 ± 0.5), compared to Cm(iii ) (log  β ′2 (Cm(N4 t bubipy)2 + ) = 8.5 ± 0.4 and log  β ′3 (Cm(N4 t bubipy)3 ) = 12.4 ± 0.6) are determined. Thus, the ligand has no preference for the complexation of An(iii ) over Ln(iii ). Additionally, no significant extraction of Am(iii ) and Eu(iii ) is observed in liquid–liquid extraction experiments due to protonation of the ligand at the experimental conditions. The experimental studies are supported by quantum chemical calculations of the free ligand and the [M(N4 t bubipy)3 ] complexes (M = Cm(iii ), Gd(iii )). The results are in excellent agreement with the experimental data and provide a deeper understanding of the complexation properties of HN4 t bubipy.